The political economy of global inequalities under the prism of COVID-19 pandemic - Roukanas, Spyros; Sklias, Pantelis (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2022)
The manifestation of the COVID-19 pandemic created unprecedented conditions at the global economic level. Ten years after the manifestation of the global financial crisis of 2007-2009, the world economy is facing the most severe economic crisis since the end of World War II. The traditional tools of monetary and fiscal policy need to face the new challenge of confronting the implications of an economic crisis that is coming from the health sector and not from an economic sector. The combined economic effects of the global financial crisis of 2007-2009 with the severe economic impact of the COVID-19 pandemic create new challenges for the economic policy that is implemented by governments and central banks. The aim of this article is to reveal the political economy of global inequalities under the prism of the COVID-19 pandemic. Developing economies are faced with more severe economic challenges in comparison to developed economies. Economic and social inequalities are going to affect the economic prospects of developing economies in the long term.